Pain Assessment in a Geriatric Psychiatry Program - Paul Stolee; Loretta M Hillier; Jacquelin Esbaugh; Nancy Bol; Laurie McKellar; Nicole Gauthier; Maggie C Gibson (Pain Research and Management)
BACKGROUND: The assessment of pain in older persons with psychiatric illness is particularly challenging for health care professionals. There are few well-tested pain assessment tools for this population.